2021
DOI: 10.1371/journal.pone.0245701
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Toxoplasma gondii infection in people with alcohol consumption in Durango, Mexico

Abstract: The seroepidemiology of infection with Toxoplasma gondii (T. gondii) in alcohol consumers is largely undeveloped. In light of this, we sought to determine the seroprevalence of T. gondii infection in alcohol consumers in Durango, Mexico, and the association of T. gondii seroprevalence with characteristics of the population studied. Anti-T. gondii IgG and IgM antibodies were searched in sera of participants using commercially available enzyme immunoassays. Bivariate and logistic regression analyses were then us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…In the present study, a significant difference in T. gondii seroprevalence was found between patients diagnosed with mental disorders concerning alcohol abuse and healthy blood donors. Our results are consistent with those found by Samojłowicz et al [40] and Estrada-Martinez et al [41] but inconsistent with the results published by Suvisaari et al [42], who found no association between T. gondii seropositivity and alcohol abuse.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, a significant difference in T. gondii seroprevalence was found between patients diagnosed with mental disorders concerning alcohol abuse and healthy blood donors. Our results are consistent with those found by Samojłowicz et al [40] and Estrada-Martinez et al [41] but inconsistent with the results published by Suvisaari et al [42], who found no association between T. gondii seropositivity and alcohol abuse.…”
Section: Discussionsupporting
confidence: 70%
“…This indicates that sex could be one of the potential risk factors in South China. Studies from other region of the world also showed the similar phenomena PLOS ONE [33,34], except some opposite results due to regional and cultural habits [35]. The difference in infection rates between male and female is speculated to be related to sex hormones [36].…”
Section: Discussionmentioning
confidence: 65%
“…Alcohol exposure can cause dysregulation of the immune system; however, the association between T. gondii infection and alcohol consumption is not well understood. In a study looking at the seroepidemiology of infection with T. gondii in Durango, Mexico, there was a positive association between alcohol consumption and anti-T. gondii IgG and IgM antibodies, specifically an 11.2% seroprevalence [93]. Additionally, those infected with T. gondii have displayed increased risky behavior due to the parasite's ability to infect and persist in the central nervous system.…”
Section: Further Evidence Linking T Gondii Infection and Alcohol Use ...mentioning
confidence: 99%